Răspuns :
a) (x+5)(x-5)
b) (2+9t)(2-9t)
c) (2+a)(4-2a+a²)
d) (c+2x)(c²-2xc+4x²)
e) [tex] \frac{1}{27}+ x^{-3} = \frac{1}{27} + \frac{1}{ x^{3} }=( \frac{1}{3}+ \frac{1}{x})( \frac{1}{9}- \frac{1}{3x}+ \frac{1}{ x^{2} } ) [/tex]
f) [tex]- c^{6} - 27x^{3}=-( c^{6}+ 27x^{3})=-( c^{2} +3x)( c^{4}- 3c^{2}x+ 9x^{2}) [/tex]
g) [tex]( \frac{1}{5} + yz^{3})( \frac{1}{25}- \frac{yz^{3} }{5}+ y^{2} z^{6}) [/tex]
h) [tex] =\frac{1}{125 m^{3} } - \frac{1}{ n^{6} }=( \frac{1}{5m}- \frac{1}{ n^{2} } )( \frac{1}{25 m^{2} }+ \frac{1}{5mn^{2} }+ \frac{1}{ n^{4} }) [/tex]
b) (2+9t)(2-9t)
c) (2+a)(4-2a+a²)
d) (c+2x)(c²-2xc+4x²)
e) [tex] \frac{1}{27}+ x^{-3} = \frac{1}{27} + \frac{1}{ x^{3} }=( \frac{1}{3}+ \frac{1}{x})( \frac{1}{9}- \frac{1}{3x}+ \frac{1}{ x^{2} } ) [/tex]
f) [tex]- c^{6} - 27x^{3}=-( c^{6}+ 27x^{3})=-( c^{2} +3x)( c^{4}- 3c^{2}x+ 9x^{2}) [/tex]
g) [tex]( \frac{1}{5} + yz^{3})( \frac{1}{25}- \frac{yz^{3} }{5}+ y^{2} z^{6}) [/tex]
h) [tex] =\frac{1}{125 m^{3} } - \frac{1}{ n^{6} }=( \frac{1}{5m}- \frac{1}{ n^{2} } )( \frac{1}{25 m^{2} }+ \frac{1}{5mn^{2} }+ \frac{1}{ n^{4} }) [/tex]
a³+b³ = (a+b)(a²-ab+b²)
a³-b³ = (a-b)(a²+ab+b²)
125m⁻³ -n⁻⁶ = 1/125m³ - 1/n⁶ = (1/5m - 1/n²)( 1/25m²+1/5mn²+1/n⁴)
a³-b³ = (a-b)(a²+ab+b²)
125m⁻³ -n⁻⁶ = 1/125m³ - 1/n⁶ = (1/5m - 1/n²)( 1/25m²+1/5mn²+1/n⁴)